Isolation and ex vivo Expansion of Human Limbal Epithelial Progenitor Cells - Polisetti, Naresh; Schlunck, Gunther; Reinhard, Thomas; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Bio-protocol, 2020)
Limbal stem cell transplantation has been used successfully to treat patients with limbal stem cell deficiency all over the world. However, long term clinical results often proved less satisfactory due to the low quality of the graft or inadequate properties of transplanted cells. To enhance the ex vivo expansion of human limbal epithelial stem or progenitor cells (LEPC) by preserving stem cell phenotype and to improve subsequent transplantation efficiency, cell-matrix interactions ex vivo should mimic the condition in vivo. The laminin isoforms preferentially expressed in the limbal niche can be used as a culture matrix for epithelial tissue engineering. We recently published the expansion of LEPC on various laminin isoforms and observed that laminin alpha 5-derived matrices support the efficient expansion of LEPC compared to tissue culture plates and other laminin isoforms by preserving stem/progenitor cell phenotype. Here, we describe an optimized protocol for the isolation of LEPC from cadaveric corneal limbal tissue by collagenase digestion and efficient expansion of LEPC using recombinant human laminin-511 E8 fragment (LN-511E8) as culture substrate.
CRIS-Team WoS Importer:2020-11-20